A pan-beta-coronavirus vaccine bearing conserved and asymptomatic B- and T-cell epitopes protects against highly pathogenic Delta and highly transmissible Omicron SARS-CoV-2 variants - Hawa Vahed; Swayam Prakash; Afshana Quadiri; Izabela Coimbra Ibraim; Etinosa Omorogieva; Swena Patel; Jimmy Tadros; Emma Jane Liao; Lauren Lau; Aziz A. Chentoufi; Anthony B. Nesburn; Baruch D. Kuppermann; et al. (Human Vaccines & Immunotherapeutics, 2025)
Over the last five years of the COVID-19 pandemic, the repetitive mutations and deletions in the SARS-CoV-2 genome, primarily targeting the Spike gene, resulted in the emergence of multiple viral variants and sub-variants. The non-updated mismatched Spike-based sub-unit vaccines are less effective due to the ability of these SARS-CoV-2 variants and sub-variants to evade vaccine-induced humoral immunity. To reduce reliance on neutralizing antibodies and prevent potential mismatches between circulating variants, sub-variants, and the vaccines, we have identified highly conserved Spike and non-Spike viral epitopes associated with protective asymptomatic B- and T-cell immune responses, respectively. We demonstrated that unvaccinated asymptomatic patients with COVID-19 recognized these conserved B- and T-cell epitopes. Using the mRNA-LNP-based antigen delivery system, we developed a multi-epitope vaccine that incorporates the conserved B-cell epitopes, CD4+ T-cell epitopes, and CD8+ T-cell epitopes. To assess the efficacy of this “asymptomatic” multi-epitope vaccine, we used the HLA-A*02:01/HLA-DRB1* 01:01-hACE-2 triple transgenic mouse model. We demonstrated that this “asymptomatic” multi-epitope vaccine conferred robust protection against infection and disease caused by the SARS-CoV-2 Delta (B.1.617.2) and Omicron (XBB.1.5) variants as assessed by: (i) prevention of weight loss, (ii) reduction of virus replication, and (iii) lung pathology. This protection was associated with: (i) strong antibody responses; and (ii) high frequency of anti-viral IFN-γ-producing CD4+ and CD8+ T-cells. These findings illustrate the possibility of developing a pan-beta-coronavirus vaccine to induce broad-spectrum protective immunity against SARS-CoV-2 variants and sub-variants by targeting highly conserved “asymptomatic” B- and T-cell epitopes identified from both structural and non-structural viral proteins.